Analisis Pertanggungjawaban Hukum Pemerintah dalam Menegakkan Pelindungan Data Pribadi di Era Digital - Khetrina Maria Angnesia; Sidi Ahyar Wiraguna (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid development of information technology in the digital era has presented new challenges in the protection of personal data. The government as the state administrator has a constitutional obligation to protect the rights of citizens, including the right to privacy. This study aims to analyze the form of government legal accountability in ensuring the protection of people's personal data amidst the increasing threat of information leaks and protection. The research method used is normative juridical with a regulatory-legislative approach as well as case studies and also the opinions of relevant experts. The research findings show that although there are legal instruments such as Law Number 27 of 2022 concerning Personal Data Protection, the effectiveness of its implementation is still limited by a number of factors, including weak supervision. The results of the analysis show that although regulations such as the Personal Data Protection Law have been present, implementation in the field still faces various obstacles, both in terms of law enforcement, public digital literacy, and transparency of permits. The government has a responsibility not only normatively, but also factually to protect personal data through policies that favor the public interest. The government is required not only to form regulations, but also to carry out supervisory and enforcement functions effectively and accountably, and sustainably in order to protect fundamental rights. Therefore, the government's legal responsibility must be realized through consistent real actions in ensuring the security of personal data in the digital era.